Kegagalan Revolusi Mental dan Penataan Birokrasi - Faisyal, Faisyal; Babys, Salomon A.M. (Oratio Directa (Prodi Ilmu Komunikasi), 2025)
The phenomenon of corruption in the bureaucracy is like the tip of the iceberg. If it persists for a long time, it could threaten the survival of the nation. The economy will undoubtedly be disrupted, and development will inevitably be hampered. To reduce corruption in the bureaucracy, around December 2016, Jokowi launched the Mental Revolution program. The program's goals and targets are excellent: creating a clean and serving bureaucracy. The mindset and behavior of wanting to be served become a willingness to serve, from unproductive to productive, and from corrupt to non-corrupt. Corruption, which has given rise to rent-seeking behavior, has also occurred within the bureaucracy. Using bureaucratic power to seek material gain, leads to a rent-seeking society.Keywords: Corruption, Mental Revolution, Rent-Seeking Bureaucracy